Disharmoni Kebijakan Prioritas BUMN dalam UU Persaingan Usaha terhadap Prinsip Level Playing Field di Indonesia - Muhammad Baihaqy Ash Shiddiqi; Akhmad Farroh Hasan (MLIJo: Journal of Law and Islamic Thought, 2026)
The existence of Badan Usaha Milik Negara (BUMN) in the Indonesian economic system bears a constitutional mandate under Pasal 33 Undang-Undang Dasar 1945 to control production sectors vital to the state and crucial for the public livelihood. However, following the enforcement of Peraturan Menteri BUMN Nomor PER-2/MBU/3/2023 tentang Pedoman Tata Kelola dan Kegiatan Terpadu BUMN which intensifies the "Sinergi BUMN" policy a severe normative tension has emerged against Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Priority policies and direct appointments inter-BUMN trigger a regulatory asymmetry that damages the level playing field principle and violates the global doctrine of competitive neutrality. Utilizing a normative legal research method with statutory, conceptual, and comparative approaches, this article dissects the constitutional boundaries of BUMN immunity, analyzes contemporary regulatory conflicts, and offers a concrete solution through the institutionalization of an Ex-Ante Competition Assessment (comprising Regulatory Impact Assessment and a Competition Checklist), drawing insights from the legal frameworks of Australia, Singapore, and China.